2014
DOI: 10.1093/nar/gku1302
|View full text |Cite
|
Sign up to set email alerts
|

An archaeal CRISPR type III-B system exhibiting distinctive RNA targeting features and mediating dual RNA and DNA interference

Abstract: CRISPR-Cas systems provide a small RNA-based mechanism to defend against invasive genetic elements in archaea and bacteria. To investigate the in vivo mechanism of RNA interference by two type III-B systems (Cmr-α and Cmr-β) in Sulfolobus islandicus, a genetic assay was developed using plasmids carrying an artificial mini-CRISPR (AC) locus with a single spacer. After pAC plasmids were introduced into different strains, Northern analyses confirmed that mature crRNAs were produced from the plasmid-borne CRISPR l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
168
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 79 publications
6
168
0
Order By: Relevance
“…The immunopurified Type III-B Cmr complexes contain all Cmr proteins (Cmr1-6) that have been previously identified by conventional column chromatography purification (Hale et al 2009) and shown to be individually required for Cmr RNA targeting activity in vitro using recombinant proteins (Hale et al 2009(Hale et al , 2012. DNA targeting in addition to RNA targeting activity has been found for the Cmr complex in Sulfolobus islandicus (Deng et al 2013;Peng et al 2015). Similar to the Cmr complex, immunopurified Type I-A (Csa) crRNPs were found to contain each of the encoded Csa proteins with the exception of Csa3, a protein thought to be a transcriptional regulator of csa genes rather than a component of the Csa effector complex (Lintner et al 2011a;Makarova et al 2014).…”
Section: Cas Protein Composition and Functional Roles Of Csa And Cst mentioning
confidence: 98%
See 1 more Smart Citation
“…The immunopurified Type III-B Cmr complexes contain all Cmr proteins (Cmr1-6) that have been previously identified by conventional column chromatography purification (Hale et al 2009) and shown to be individually required for Cmr RNA targeting activity in vitro using recombinant proteins (Hale et al 2009(Hale et al , 2012. DNA targeting in addition to RNA targeting activity has been found for the Cmr complex in Sulfolobus islandicus (Deng et al 2013;Peng et al 2015). Similar to the Cmr complex, immunopurified Type I-A (Csa) crRNPs were found to contain each of the encoded Csa proteins with the exception of Csa3, a protein thought to be a transcriptional regulator of csa genes rather than a component of the Csa effector complex (Lintner et al 2011a;Makarova et al 2014).…”
Section: Cas Protein Composition and Functional Roles Of Csa And Cst mentioning
confidence: 98%
“…CRISPR RNAs (crRNAs) are produced by processing of CRISPR locus transcripts that arise from promoter elements in the leader region (Jansen et al 2002;Tang et al 2002). Each crRNA contains a guide region comprised of invader-derived sequences that allow crRNA-Cas protein effector complexes to recognize and destroy invader nucleic acids (Barrangou et al 2007;Marraffini and Sontheimer 2008;Hale et al 2009Hale et al , 2012Garneau et al 2010;Jore et al 2011;Lintner et al 2011b;Wiedenheft et al 2011a;Fischer et al 2012;Gasiunas et al 2012;Jinek et al 2012;Westra et al 2012a;Elmore et al 2013;Maier et al 2013;Mulepati and Bailey 2013;Peng et al 2013Peng et al , 2015Sinkunas et al 2013;Plagens et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The type III-A CRISPR-Cas system is believed to target DNA based on its ability to interfere with plasmid transformation and conjugation in Staphylococcus epidermidis (Marraffini and Sontheimer 2008;Hatoum-Aslan et al 2013. DNA targeting by the S. epidermidis CRISPR-Cas system requires active transcription of the target DNA, thereby enabling conditional tolerance of temperate phages (Goldberg et al 2014;Peng et al 2015). Purified Csm complexes from Streptococcus thermophilus and Thermus thermophilus cleave ssRNA in vitro by a mechanism similar to that of the Cmr complex (Staals et al 2014;Tamulaitis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Type III-A typically contains 6 different proteins but the nuclease is not yet identified. Csm complexes target DNA (Marraffini and Sontheimer, 2008) and CMR complexes target RNA (Zebec et al, 2014), but targeting RNA and DNA by the same Cmr complex has been found in S. islandicus (Peng et al, 2015). Type II systems require the Cas9 protein, crRNA and also a tracrRNA bound to Cas9.…”
Section: Crispr/cas In Prokaryotesmentioning
confidence: 86%